2014
DOI: 10.1158/1078-0432.ccr-14-0970
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Lumican Inhibits Pancreatic Cancer Cell Growth and Is Associated with Prolonged Survival after Surgery

Abstract: Purpose To evaluate the relevance between lumican expression patterns and the clinical course of PDAC patients, and to investigate the role of lumican in PDAC progression. Experimental Design 131 patient tumors were chosen for tissue microarray staining and Cox regression analysis was used to test the associations between lumican expression and clinical, pathologic, and oncologic outcomes in all patients. Primary PDAC cells and recombinant human lumican protein were used to establish a working model to mimic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 47 publications
(45 reference statements)
3
73
2
Order By: Relevance
“…Using the Kaplan-Meier method, the median survival of the stromal lumican high group (≥DAB mean) was 16.05 months compared to 10.2 months for the stromal lumican low patient group (<DAB mean) (Figure 1d). This trend is consistent with our previous observations (19) although the difference did not reach statistically significance (p=0.32) due to the small sample size. The clinicopathologic characteristics in the patient groups with high or low stromal lumican expression was also compared and is displayed in Supplementary Table 2.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Using the Kaplan-Meier method, the median survival of the stromal lumican high group (≥DAB mean) was 16.05 months compared to 10.2 months for the stromal lumican low patient group (<DAB mean) (Figure 1d). This trend is consistent with our previous observations (19) although the difference did not reach statistically significance (p=0.32) due to the small sample size. The clinicopathologic characteristics in the patient groups with high or low stromal lumican expression was also compared and is displayed in Supplementary Table 2.…”
Section: Resultssupporting
confidence: 92%
“…In previous work, we identified that cancer-related survival in pancreatic cancer patients is associated with the amount and distribution of lumican within the primary PDAC tumor (19). In this study we performed IHC staining of a unique cohort of PDAC tumor specimens and observed the presence of lumican within both cancer cells as well as the stroma (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty to fifty micrograms of protein was used for western blotting analysis. Detailed methods can be found in our previous publication (26). …”
Section: Methodsmentioning
confidence: 99%
“…The study showed that patients who had PG localized mostly in the stromal rather than the epithelial area also presented a decrease in metastatic recurrence. In vivo model showed that lumican decreased EGFR (epidermal growth factor receptor) and HIF-1α expression via Akt; cancer cells with enhanced HIF-1α activity became resistant to lumican-induced inhibition of glucose consumption and apoptosis [180]. Therefore, lumican acts against pancreatic cancer cell development, protecting the microenvironment from the consequences of HIF-1α, and is correlated with tumor progression.…”
Section: Alterations In the Cell–cell And Cell–extracellular Matrix Imentioning
confidence: 99%